Activity of a Sub-cutaneously Administered Novel Mixed Micellar Formulation of Argatroban in Rat and Rabbit Models of Venous Thrombosis - Berry, Christopher N.; Visconte, Catherine; Lecoffre, Catherine; Lochot, Sylvette; Girard, Denise (Thrombosis and Haemostasis, 2000)
We studied the antithrombotic activity of a mixed micellar formulation containing 14 mg/ml argatroban administered by the subcutaneous (s. c.) route in rat and rabbit models of venous thrombosis. The effects on bleeding time in the rat tail transection bleeding time test were also studied. In a tissue factor-dependent arterio-venous shunt model, argatroban treatment led to dose-dependent reduction in thrombus weight with an estimated ID50 of 1.8 mg/kg s. c. In the same model, heparin had an estimated ID50 of 179 IU/kg. The antithrombotic activity of argatroban was accompanied by increases in the thrombin and ecarin clotting times but not the aPTT, whereas heparin increased the thrombin time and aPTT but not the ecarin clotting times. Argatroban also inhibited thrombus formation in a rabbit model of thromboplastin + stasis induced thrombosis in the rabbit jugular vein with an estimated ID50 of 1 mg/kg s. c. When tested in the rat tail transection bleeding time test, the mixed micellar formulation of argatroban caused significant increases in the bleeding time as from 8 mg/kg s. c., while heparin significantly increased the bleeding time at 800 U/kg. Mixed micellar argatroban appears to have a superior safety margin to heparin in terms of antithrombotic efficacy and bleeding risk.Thus, a mixed micellar formulation of argatroban, which markedly enhances its solubility, could be useful as a potential antithrombotic agent for subcutaneous administration.
Keywords: Argatroban mixed micelles; rat venous thrombosis; rabbit venous thrombosis; tail-transection bleeding time